Konsep Pendidikan Integrasi di SMP Ya'qubiyah Kabupaten Malang - Hilmy, Ahmad Riyadzul (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
Integrated education is a concept of education management by combining several curriculum structures into an educational institution with to achieving the goals, visions and missions set and approved by members of the educational institution. This is done as an effort to answer the challenges of the 4.0 era which is increasingly complex and it is not enough to master one particular field or group of lessons so that it is a necessity student always survive in this modern era. This research aims to find out and explain to public about the concept of integration education applied by the Ya'qubiyah Junior High School located in Wajak District, Malang Regency. This research is a qualitative research with case research in order to find phenomena that actually occur in the research location so that this research concludes that the institution combines the national curriculum with the pesantren curriculum and separates the management of curriculum management into three main parts to maximize the development and management of an integrated curriculum and there is a special policy that requires students to master the two sciences that characterize the institution.